Multilayered Analysis of Urban Mobility - Gubert, Fernanda R.; Munaretto, Anelise; Silva, Thiago H. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2022)
This study analyzes the urban mobility of Curitiba through the use of public transit by the population divided into socioeconomic strata. To study the established mobility graph and its spatio-temporal patterns, a multilayered approach called Multi-Aspect Graph (MAG) with four aspects is applied. The results detail patterns that cannot be observed in a traditional graph, such as the most frequent routes and the most central points of the city, taking into account all the modeled aspects. The model used allows a strategic understanding of the use of the beneficial public transit system for different applications, such as actions in emergencies and outbreaks of rapidly contagious diseases.